2018
DOI: 10.1038/s41598-018-21567-8
|View full text |Cite|
|
Sign up to set email alerts
|

Zearalenone altered the cytoskeletal structure via ER stress- autophagy- oxidative stress pathway in mouse TM4 Sertoli cells

Abstract: The aim of this study was to investigate the molecular mechanisms of the destruction of cytoskeletal structure by Zearalenone (ZEA) in mouse-derived TM4 cells. In order to investigate the role of autophagy, oxidative stress and endoplasmic reticulum(ER) stress in the process of destruction of cytoskeletal structure, the effects of ZEA on the cell viability, cytoskeletal structure, autophagy, oxidative stress, ER stress, MAPK and PI3K- AKT- mTOR signaling pathways were studied. The data demonstrated that ZEA da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 47 publications
3
38
0
1
Order By: Relevance
“…Therefore, the increase in cell death, which was observed in cells treated with 20 and 40 µg/mL of ZEN, may be at least in part due to the overproduction of autophagic vesicles. Similar to our data, ZEN could induce autophagy by increasing beclin1, LC3-II, and autophagosomes in mouse and rat testicular cells [42,43]. Other potential mechanisms were reported in a recent publication where ZEN could induce the expression of cytochrome P450 reductase and oxidative stress, resulting in autophagy in porcine intestinal epithelial cells [44].…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, the increase in cell death, which was observed in cells treated with 20 and 40 µg/mL of ZEN, may be at least in part due to the overproduction of autophagic vesicles. Similar to our data, ZEN could induce autophagy by increasing beclin1, LC3-II, and autophagosomes in mouse and rat testicular cells [42,43]. Other potential mechanisms were reported in a recent publication where ZEN could induce the expression of cytochrome P450 reductase and oxidative stress, resulting in autophagy in porcine intestinal epithelial cells [44].…”
Section: Discussionsupporting
confidence: 91%
“…In DU-145 cells, a similar increase was observed in p-p44-42 expression. The induction of the PI3K/Akt signaling pathway was previously associated both with ZEA-induced autophagy and oxidative stress [25,26]. Although the activation of the PI3K/Akt signaling pathway is mostly associated with the proliferation of cancer cells, similar to others, we observed increased phosphorylation of Akt in cells treated with ZEA + BAY as well as ZEA + BAY + PHTPP in LNCaP cells.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies have shown that the ER stress pathway has been reported to participate in oxidative damage and apoptosis induced by ZEN 22 24 , 46 . To provide further evidence that the A2 fermentation broth exerts a protective effect from ZEN-induced kidney injury, we explored whether the A2 fermentation broth could decrease both ER stress and apoptosis induced by ZEN.…”
Section: Discussionmentioning
confidence: 99%